Long‐term in vitro and in vivo effects of γ‐irradiated BCG on innate and adaptive immunity. Issue 6 (16th June 2015) - Arts, Rob J. W.; Blok, Bastiaan A.; Aaby, Peter; Joosten, Leo A. B.; de Jong, Dirk; van der Meer, Jos W. M.; Benn, Christine Stabell; van Crevel, Reinout; Netea, Mihai G.
Abstract : γ‐irradiated BCG induces heterologous immunity, but nottrained immunity in vivo, in contrast to BCG which induces both. Abstract : BCG vaccination is associated with a reduced mortality from nonmycobacterial infections. This is likely to be mediated by a combination of innate‐immune memory ("trained immunity") and heterologous effects on adaptive immunity. As such, BCG could be used to boost host immunity but not in immunocompromised hosts, as it is a live, attenuated vaccine. Therefore, we assessed whether killed γBCG has similar potentiating effects. In an in vitro model of trained immunity, human monocytes were incubated with γBCG for 24 h and restimulated after 6 d. Cytokine production and the role of pattern recognition receptors and histone methylation markers were assessed. The in vivo effects of γBCG vaccination were studied in a proof‐of‐principle trial in 15 healthy volunteers. γBCG induced trained immunity in vitro via the NOD2 receptor pathway and up‐regulation of H3K4me3 histone methylation. However, these effects were less strong than those induced by live BCG. γBCG vaccination in volunteers had only minimal effects on innate immunity, whereas a significant increase in heterologous Th1/Th17 immunity was observed. Our results indicate that γBCG induces long‐term training of innate immunity in vitro. In vivo, γBCG induces mainly heterologous effects on the adaptive‐immune system, whereas effects on innate cytokine production are limited.